2020
DOI: 10.1525/collabra.278
|View full text |Cite
|
Sign up to set email alerts
|

Recalling Experiences: Looking at Momentary, Retrospective and Global Assessments of Relationship Satisfaction

Abstract: Relationship satisfaction can be assessed in retrospection, as a global evaluation, or as a momentary state. In two experience sampling studies (N = 130, N = 510) the specificities of these assessment modalities are examined. We show that 1) compared to other summary statistics like the median, the mean of relationship satisfaction states describes retrospective and global evaluations best (but the difference to some other summary statistics was negligible); 2) retrospection introduces an overestimation of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 88 publications
0
16
0
1
Order By: Relevance
“…One study on recall bias in ratings of relationship satisfaction suggests that couples generally tend to rate past relationship satisfaction more negatively that it actually was [ 46 ], resulting in a trend for perceived satisfaction improvement rather than deterioration over time. Similarly, a study by Zygar-Hoffmann and Schönbrodt [ 28 ] showed that retrospective reports of annoyance toward the partner were overestimated, whereas the retrospective assessment of relationship satisfaction was quite accurate overall. If our results were affected by the recall bias as identified in previous research, they would have under estimated the degree of decline in relationship satisfaction.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…One study on recall bias in ratings of relationship satisfaction suggests that couples generally tend to rate past relationship satisfaction more negatively that it actually was [ 46 ], resulting in a trend for perceived satisfaction improvement rather than deterioration over time. Similarly, a study by Zygar-Hoffmann and Schönbrodt [ 28 ] showed that retrospective reports of annoyance toward the partner were overestimated, whereas the retrospective assessment of relationship satisfaction was quite accurate overall. If our results were affected by the recall bias as identified in previous research, they would have under estimated the degree of decline in relationship satisfaction.…”
Section: Discussionmentioning
confidence: 95%
“…terror attacks; other studies on the impact of the COVID-19 pandemic [ 25 27 ]). Although retrospective data have their limitations, they have shown to be generally quite accurate in the case of relationship satisfaction [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the reciprocal exchange process, work on state relationship satisfaction suggests that the state is determined by reciprocal affection between relationship partners (Zygar et al, 2018). State relationship satisfaction is distinct, yet correlated with global assessments of relationship quality (Zygar-Hoffmann & Schönbrodt, 2020). Examination of state relationship satisfaction has provided evidence regarding the significant role of state-like constructs in the underlying process when similar, trait-like constructs offered mixed evidence (i.e., Zygar et al, 2018) similar to the limited understanding of trait negative affect in the LMX relationship (see Dulebohn et al, 2012).…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…The present research used data from an experience sampling study with German couples. The data are available as a scientific use-file (Zygar-Hoffmann et al, 2020a ) and have been used in previous publications (Pusch et al, 2020 ; Zygar-Hoffmann and Schönbrodt, 2020 ; Zygar-Hoffmann et al, 2020b ; Schönbrodt et al, 2021 ). However, none of these previous publications addressed the hypotheses tested in the present research, but focused on other hypotheses.…”
Section: Methodsmentioning
confidence: 99%